Kepatuhan Diet dan Asupan Protein terhadap Kadar Glukosa Darah Puasa Pasien Diabetes Melitus Tipe 2 di RSUD dr. Iskak - Farhana Tontowi; Satwika Arya Pratama; Choirul Anna Nur Afifah; Lini Anisfatus Sholihah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The management of blood glucose levels in individuals diagnosed with diabetes mellitus is a multifaceted process that involves the integration of pharmacological therapy and evidence-based nutritional interventions. Among these strategies, nutritional therapy plays a pivotal role in achieving optimal glycemic control and preventing diabetes-related complications. The success of nutritional therapy is closely tied to the individual’s adherence to prescribed dietary guidelines and the ability to meet adequate protein intake as recommended by healthcare providers. Protein is essential not only for maintaining muscle mass and supporting metabolic functions but also for its role in stabilizing blood glucose levels through slower glucose absorption and enhanced satiety. This study was conducted to investigate the relationship between dietary adherence and adequate protein intake with fasting blood glucose (FBG) levels among outpatients diagnosed with type 2 diabetes mellitus at RSUD dr. Iskak Tulungagung. A quantitative research method with a cross-sectional design was employed, involving 26 respondents selected using a non-probability sampling technique. Data collection utilized structured questionnaires to assess dietary compliance, interview forms to capture dietary behavior and protein intake patterns, and medical record documentation to obtain accurate FBG measurements. Statistical analyses included Pearson correlation tests for normally distributed data and Spearman rho tests for non-normally distributed data, ensuring appropriate analytical rigor. The results indicated a significant negative correlation between both dietary adherence and adequate protein intake with fasting blood glucose levels. This finding suggests that individuals who consistently follow dietary recommendations and consume sufficient protein tend to exhibit lower FBG values, indicating better glycemic control. Such results underscore the importance of not only emphasizing dietary compliance but also ensuring protein adequacy in daily nutritional plans for type 2 diabetes patients. These findings have practical implications for diabetes management programs, highlighting the necessity of sustained patient education, regular counseling, and individualized meal planning.